Structural change for equality : an integrated approach to development (UN ECLAC SantiagoCL, 2012)
Sets out the continuing vision of equality for the development of the region on the threshold of the second decade of the twenty-first century. Considers equality as a guiding principle, giving direction as a means of spreading capacity-building, job opportunities and access to social benefits and safety nets throughout the society. Also views equality as the bedrock of citizen participation, essential for the exercise of civil, political, social and environmental rights.
Keywords: ECONOMIC REFORM